Analisis Yuridis Atas Pertanggungjawaban Pengelola Parkir Dalam Perspektif Hukum Perlindungan Konsumen di Kecamatan Coblong, Kota Bandung - Aryawinata, Muhammad Brian; Muhammad Taqiyudin Mubarok,; Amelia, Nashita; Aqilah, Rifa (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study analyzes the legal liability of parking managers from the perspective of consumer protection law in Coblong District, Bandung City. The research is based on the weak implementation of parking managers’ responsibility for the security of consumers’ vehicles, even though parking payments imply an agreement to provide such protection. Using a qualitative approach through interviews with five parking managers and ten consumers across five locations, this study explores the levels of knowledge, understanding, attitudes, and legal behavior of parking managers. The results show that while parking managers demonstrate a fair level of legal awareness regarding their duties and responsibilities, they lack comprehensive understanding of consumer rights as regulated in Law No. 8 of 1999 on Consumer Protection. Meanwhile, most consumers are unaware of their legal rights regarding vehicle security and complaint mechanisms. This imbalance creates legal uncertainty and weakens consumer protection. Therefore, stricter regulation and supervision are needed to strengthen the accountability of parking managers and to enhance public legal awareness in the use of parking services.